Resistance of High-Volume Fly Ash Self-Compacting Concrete to Internal Sulfate Attack - Tareq Al-Attar; Ahmed Taha (Engineering and Technology Journal, 2018)
This paper investigates the durability of high-volume Fly ash self-compacting concrete, HVFASCC that exposed to internal sulfate attack. At the present work, HVFASCC was produced with two Fly ash replacements: 50 and 60% by weight of Portland cement. The internal sulfate attack was simulated by adding natural gypsum (CaSO4) that contain ion (SO3-2) to fine aggregate by two weight percentages: 1 and 2%. Limestone dust was used as filler with a content of 100 kg/m3. The cementitious materials, cement and Fly ash, content was 400 kg/m3 and the water to powder ratio for the studied mixes was 0.34 by weight. To ensure the self-compact ability of the mixes, slump flow, T500, V-funnel and L-box tests were done. The Compressive, Splitting and Flexural strength Tests were extended to the age of 240 days. The results showed that there is no significant difference between 1 and 2% of SO3 content on the behavior of all mixes. The presence of limestone powder in the paste solution could have a role in stabilizing ettringite and reducing paste porosity at early ages. At later age, 240 days, the harmful effect of SO3 is diminished and that may be caused by the depletion of gypsum and the dominant product will be calcium monosulfoluminate hydrates instead of calcium sulfoaluminate hydrates.